Pister et modéliser le développement professionnel. Étude de la transformation de l'activité de personnels de l'éducation dans des situations typiques et/ou critiques - Luc Ria (Nantes Université, 2023)
For training purposes, the Neopass© program tracks and models the professional development of educational actors. According to an enactive approach of the activity, three methodologies are mobilized to account for the transformations of the activity in typical and/or critical work situations: a) the observed transformation of the activity of a beginning teacher, b) the declared transformation of the activity of a beginning head teacher and c) the accompanied transformation of the activity of an experienced professor in university. The longitudinal study of the components of their activities reveals fundamental changes in their ways of perceiving, interpreting and acting in the same work situations. These bifurcations of the activity, as markers of professional development, constitute resources for peer training.